Psychometric validation of the sibling inventory of behavior in three- to six-year-old Chinese children - Xu, Huiyan; Wang, Zhenlin; Gao, Xiaozi; Wang, Xiaoying; Wu, Qiong (Frontiers in Psychology, 2023)
With increasing attention on sibling relationship studies in China, one problem that has been neglected is the limited validation of instruments used to assess these relationships. The present study evaluated the psychometric properties of the Sibling Inventory of Behavior to measure Chinese children’s sibling relationships using a stratified random sample of 590 parents of three- to six-year-olds in three economic regions. The confirmatory factor analysis obtained an adequate fit, suggesting that the Chinese version of the instrument had a six-factor structure (i.e., Companionship, Empathy, Teaching, Rivalry, Aggression, and Avoidance). It demonstrated satisfactory internal consistency as well as test-retest reliability. Results of discriminant, convergent, and criterion-related validity test also fulfilled psychometric requirements. Furthermore, the residual measurement invariance across regions was discovered. Given the importance, emergence, and tendency of sibling studies in China, having a reliable and valid instrument with robust psychometric properties is essential and impactful.